2020
DOI: 10.1177/0886260520967140
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Roles of Intimate Partner Violence, Stress, and Social Support on Depressive Symptoms Among Thai Women

Abstract: Prior research has shown that intimate partner violence (IPV), stress, and social support are associated with depressive symptoms. However, a possible mediating role of these variables linking depressive symptoms has not been fully investigated in Thailand. This study was conducted to assess the mediating roles of IPV, stress, and social support in the relationships between childhood abuse (CA), number of sexual partners (NSP), and depressive symptoms among 400 Thai women attending gynecology clinics. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
1
0
0
Order By: Relevance
“…Participants who had a family history of mental illness were 5.08 times more likely to have antenatal common mental disorders than their counterparts. This nding is supported by previous studies done in Ethiopia and other countries (14,17,(53)(54)(55) Having a family history of mental disorders increases the risk of developing mental illness in the long run of a person's life. This may be the genetic and psychological basis of mental illness, and additionally, studies have suggested that those with a family history of mental illness are more likely to develop CMD (58).…”
Section: Discussionsupporting
confidence: 80%
“…Participants who had a family history of mental illness were 5.08 times more likely to have antenatal common mental disorders than their counterparts. This nding is supported by previous studies done in Ethiopia and other countries (14,17,(53)(54)(55) Having a family history of mental disorders increases the risk of developing mental illness in the long run of a person's life. This may be the genetic and psychological basis of mental illness, and additionally, studies have suggested that those with a family history of mental illness are more likely to develop CMD (58).…”
Section: Discussionsupporting
confidence: 80%